The clinical features of the overlap between COPD and asthma - Hardin, Megan; Silverman, Edwin K; Barr, R Graham; Hansel, Nadia N; Schroeder, Joyce D; Make, Barry J; Crapo, James D; Hersh, Craig P (Respiratory research, 2011)
The coexistence of COPD and asthma is widely recognized but has not been well described. This study characterizes clinical features, spirometry, and chest CT scans of smoking subjects with both COPD and asthma. We performed a cross-sectional study comparing subjects with COPD and asthma to subjects with COPD alone in the COPDGene Study. 119 (13%) of 915 subjects with COPD reported a history of physician-diagnosed asthma. These subjects were younger (61.3 vs 64.7 years old, p=0.0001) with lower lifetime smoking intensity (43.7 vs 55.1 pack years, p=0.0001). More African-Americans reported a history of asthma (33.6% vs 15.6%, p<0.0001). Subjects with COPD and asthma demonstrated worse disease-related quality of life, were more likely to have had a severe COPD exacerbation in the past year, and were more likely to experience frequent exacerbations (OR 3.55 [2.19, 5.75], p<0.0001). Subjects with COPD and asthma demonstrated greater gas-trapping on chest CT. There were no differences in spirometry or CT measurements of emphysema or airway wall thickness. Subjects with COPD and asthma represent a relevant clinical population, with worse health-related quality of life. They experience more frequent and severe respiratory exacerbations despite younger age and reduced lifetime smoking history. ClinicalTrials.gov: NCT00608764.